The Effects of Dexamethasone on Human Patellar Tendon Stem Cells: Implications for Dexamethasone Treatment of Tendon Injury - Zhang, Jianying (2012)
Injection of Dexamethasone (Dex) is commonly used in clinics to treat tendon injury such as tendinopathy because of its anti-inflammatory capabilities. However, serious adverse effects have been reported as a result of Dex treatment, such as impaired tendon healing and tendon rupture. Using both in vitro and in vivo approaches, this study was to determine the effects of Dex treatment on the proliferation and differentiation of human tendon stem cells (hTSCs), which can directly impact tendon healing. We found that Dex treatment stimulated cell proliferation at lower concentrations (< 1000 nM), whereas a high concentration (1000 nM) decreased cell proliferation. Moreover, at all concentrations used (5, 10, 100, and 1000 nM), Dex treatment induced non-tenocyte differentiation of hTSCs, as evidenced by a change in cell shape, a nearly complete suppression of collagen type I expression, and an upregulation of non-tenocyte related genes (PPARγ and Sox-9), which was especially evident when higher concentrations (> 10 nM) of Dex were used. Implantation of Dex-treated hTSCs for a short time (3 weeks) resulted in the extensive formation of fatty tissues, cartilage-like tissues, and bony tissues. These findings suggest that Dex treatment in clinics may cause a paradoxical effect on the injured tendons it is supposed to treat: by inducing non-tenocyte differentiation of hTSCs, Dex treatment depletes the stem cell pool and leads to the formation of non-tendinous tissues (e.g. fatty and cartilage-like tissues), which make tendon susceptible to rupture.